Ecologia reprodutiva de Hyalinobatrachium cappellei (Anura: Centrolenidae) e Trachycephalus cunauaru (Anura: Hylidae) na Amazônia Meridional - Noronha, Janaina da Costa de (2018)
The Amazon has the largest diversity of anuran amphibians on the planet. The environmental complexity of the region allowed the evolution of a series of reproductive modes for the group. The species of Amazonian anurans Hyalinobatrachium cappellei and Trachycephalus cunauaru use alternative reproductive modes in which eggs, the most vulnerable phase of the reproductive cycle, are not deposited in terrestrial pools, thus remaining protected from potential aquatic predators. To verify the ecological factors that influence the reproduction of both species, we sampled between the years 2014 and 2017 in an area of the Meridional Amazon in Mato Grosso, Brazil. The species Hyalinobatrachium cappellei deposited the eggs in leaves hanging over water bodies, until the hatching period the male remained close to clutches for egg attendance. After stage 25 the tadpoles hatch, drop into the water and complete the metamorphosis. For Hyalinobatrachium cappellei we analyzed if the environmental characteristics of the reproductive sites were correlated with the number of eggs and clutches and if males with one or more existing clutches at reproductive sites accumulate more new clutches than those males initially without clutches. On the other hand, the development of eggs and larvae of the species Trachycephalus cunauaru occurs in tree holes that accumulate water, known as phytotelmatas, generally located more than 20 meters high. For the species we related chemical and physical parameters of phytotelmatas with the presence and absence of tadpoles; we analyze if these parameters change during the four months of a rainy season, we register behavioral data from the installation of artificial reproductive sites and we describe the larval development of the species compared to published researches. In addition, we collected new data related to the natural history of both species, contributing to the knowledge of the anurofauna of the Southern Amazon, a megadiverse region and threatened by human actions.